Synthesis and Characterization of New Complex Salts of some Transition Metals with Pyrrolium Salts - Nabeel H.Buttrus; Isra A.Saeed (College of Education for Pure Sciences, 2005)
The preparation of series of complex chloride of the type R2[M"C14] or R2[M"'C16], when R = M" = Mn, Co, Ni, Cu , Zn, M'" = Fe, and Cr has been carried out. The conductivity, IR, Uv-visible spectra, magnetic susceptibility and elemental microanalysis of pyrrolium complex salts have been studied and it is concluded that tetrachloro complex salts of Mn", Co", Ni", Cu" have tetrahedral geometry, while Cr1" and Fe1" are hexa chloro complex salts were obtained and have octahedral geometry